Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1523/eneuro.0133-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Crmp1 Phosphorylation at Ser522 Ameliorates Motor Function and Neuronal Pathology in Amyotrophic Lateral Sclerosis Model Mice

Abstract: Amyotrophic lateral sclerosis (ALS) is a rapidly progressive and fatal neurodegenerative disorder that affects upper and lower motor neurons; however, its pathomechanism has not been fully elucidated. Using a comprehensive phosphoproteomic approach, we have identified elevated phosphorylation of Collapsin response mediator protein 1 (Crmp1) at serine 522 in the lumbar spinal cord of ALS model mice overexpressing a human superoxide dismutase mutant (SOD1 G93A ). We investigated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Sema3A is highly expressed in Schwann cells at the distal ends of motor neuron axons in G93A-SOD1 ALS mice (20). Furthermore, blockade of Sema3A signaling by anti-NRP1 antibody (21) or inhibition of CRMP1 phosphorylation (23) mitigates NMJ damage and restores muscle strength in the G93A-SOD1 mouse model of ALS. These findings are consistent with ALS pathogenesis, which is characterized by progressive distal axonopathy in motor neurons that precedes degeneration of cell bodies (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sema3A is highly expressed in Schwann cells at the distal ends of motor neuron axons in G93A-SOD1 ALS mice (20). Furthermore, blockade of Sema3A signaling by anti-NRP1 antibody (21) or inhibition of CRMP1 phosphorylation (23) mitigates NMJ damage and restores muscle strength in the G93A-SOD1 mouse model of ALS. These findings are consistent with ALS pathogenesis, which is characterized by progressive distal axonopathy in motor neurons that precedes degeneration of cell bodies (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that CRMP1 is involved in the pathogenesis of neurological diseases such as Huntington's disease ( 34 ) and schizophrenia ( 35 , 36 ). Although its contribution in ALS had not been elucidated except that mass spectrometry data suggests CRMP1 is one of the interacting partners of the Met337Val TDP-43 mutant ( 37 ), we recently have shown that CRMP1 modulates phenotypes of G93A-SOD1 mice ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation